Comeback for quinoa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
There is a rivival of interest in the amaranth known as quinoa, Chenopodium quinoa. Amaranths were traditionally grown in upland regions of Latin America at the time of the Aztec empire. After the arrival of the Europeans the crop was gradually...